2018
DOI: 10.4103/apjon.apjon_17_18
|View full text |Cite
|
Sign up to set email alerts
|

A Concept Analysis of Self-Management of Cancer Pain

Abstract: The objective of the study was to conduct a concept analysis of “self-management of cancer pain” to develop a theoretical definition of the concept and identify its attributes, antecedents, and outcomes. The Rodgers' evolutionary model of concept analysis was used. Literature published from January 2000 to February 2017 containing the terms, “cancer pain” and “self-management” in their title and/or abstract was assessed. Twenty-seven studies were selected for this analysis. Self-management of cancer pain is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 29 publications
0
35
0
4
Order By: Relevance
“…This shift from acute to chronic care brings emphasis to self-management of cancer, where patients need to have an active and informed role in managing psychological, physical and social aspects of their health. As chronic disease management will continue to be an important component of health care, the identification of self-management processes for cancer [4] can greatly help to guide clinical practice and future research in supporting self-management efforts and integrated care.…”
Section: Introductionmentioning
confidence: 99%
“…This shift from acute to chronic care brings emphasis to self-management of cancer, where patients need to have an active and informed role in managing psychological, physical and social aspects of their health. As chronic disease management will continue to be an important component of health care, the identification of self-management processes for cancer [4] can greatly help to guide clinical practice and future research in supporting self-management efforts and integrated care.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to the definition by Yamanaka [12], self-management of cancer pain was defined as "the process in which patients with cancer pain make the decision to manage their pain, enhance their self-efficacy by solving problems caused by pain, and incorporate pain-relieving strategies into daily life, through interactions with healthcare professionals. "…”
Section: Self-management Of Cancer Painmentioning
confidence: 99%
“…Patients participating in this study were self-regulating the analgesic medications, and it has been reported that the antecedents of self -management of cancer pain were physical functions, cognitive abilities, motivation, undergoing medical treatment for pain, receiving individualized training, subject to support by family and healthcare professionals, and in possession of health literacy [12].…”
Section: Suggestions For Nursing Practicementioning
confidence: 99%
“…Self-management of cancer pain can be defined as “the process in which patients with cancer pain make the decision to manage their pain, enhance their self-efficacy by solving problems caused by the pain, and incorporate pain-relieving strategies into daily life, through interactions with health care professionals.” 37 Lorig and Holman 25 suggested 3 tasks of self-management interventions:(1) Managing medical treatment, including self-monitoring of pain, obtaining the prescribed pain medication, and using nonpharmacologic pain management techniques. 22 (2) Modifying and adjusting their lifestyle, employment, and behaviours to keep some amount of normalcy in life.(3) Managing emotional and psychological consequences of illness including the use of stress-coping strategies.…”
Section: Introductionmentioning
confidence: 99%